Smart Assistance for the Disabled: Design and Implementation of an Accessible Employment Service Platform Based on GPT Technology - Xiangdong, Chen; Heng, Cui; Fan, Wang; Tianshengnan, Pan; Phei Chin, Lim (2025)
The disabled population faces issues such as limited job search channels, insufficient skill matching, and social prejudice in the job market. In response to the “14th Five-Year Plan” for the protection and development of the disabled people in China, this paper designs and implements an accessible employment service platform based on GPT technology - “Smart Assistance for the Disabled”. The platform uses artificial intelligence and big data analysis to provide personalized job recommendations and intelligent skill training, as well as multimodal interaction assistance tools. It also builds a comprehensive employment service system through policy interpretation, enterprise cooperation, and psychological support modules. Adhering to the WCAG 2.1 standard, usability tests show that the platform significantly improves job search efficiency (by 42%) and employment quality for disabled people, providing an innovative solution for high-quality employment.